Comparison of the extraction efficiencies of four different solvents used in trace metal digestion of selected soils within Abakaliki, Nigeria - NO Omaka; IF Offor; ER Chukwu; U Ewuzie (Journal of Applied Sciences and Environmental Management)
Soil pollution by trace metals is one of the major global environmental challenges facing us today. Extraction methods are key to predicting plant uptake of trace metals from soil. This work seeks to compare the extraction efficiencies of EDTA, DTPA, HNO3/HClO4 and HCl/HNO3 used in the digestion of soil samples collected from 11 different locations (7 farmlands, 2 waste dumpsites and 2 sections of a mechanic workshop) within Abakaliki metropolis, between August and September 2007. Concentrations of 7 selected trace metals (Pb, Zn, Mn, Ni, Cd, Cu and Fe) were determined in the digested soil samples using atomic absorption  spectrophotometer. The concentrations (mg/kg) range, irrespective of sampling sites were: Pb (2.85-43.07; 1.42-11.49; 3.83-131.90; 1.98-184.12), Zn (0.02-3.98; 0.01-0.79; 2.25-13.22; 0.15-39.45), Mn (1.33-78.83; 0.38-14.85; 1.02-66.24; 0.84-104.39), Ni (1.15-14.10; 0.07-2.57; 2.09-49.70; 5.10-92.72), Cd (0.03-2.79; 0.01-0.61; 0.25-9.20; 0.15- 3.68), Cu (1.59-79.96; 0.65-14.33; 1.02-184.68; 1.60-134.10), Fe (6.62-149.44; 0.39-12.22; 44.95-375.27; 7.48-548.32) using EDTA, DTPA, HNO3/HClO4 and HCl/HNO3 respectively as extractanes. Results revealed that all extractants showed strong positive correlation in bringing only Cd into solution. ANOVA depicted no significant difference in mean trace metals contents of soils from mechanic workshops as extracted with all solutions, while other locations did. For risk assessment, only Cd, Ni and Pb had their values within the regulatory limits, whereas others were above the limits in all samples from different locations.